2021
DOI: 10.7455/ijfs/10.si.2021.a8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antimicrobial, Antioxidant and Cytotoxicity Properties of Selected Plant Extracts for Food Preservative Applications

Abstract: An attempt has been made to evaluate antimicrobial, antioxidant and cytotoxicity properties of extracts from onion (Allium cepa L.), garlic (Allium sativum), leaves of guava (Psidium guajava), papaya (Carica papaya), tea (Camellia sinensis), baen (Avicennia alba) and keora (Sonneratia apetala), respectively to apply as natural preservatives for tomatoes. The air-dried plant materials of the respective plant species were subjected to ethanol-methanol extraction, concentrated and stored at 4 °C before use. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…The effectiveness of neem and moringa aqueous leaf extracts in reducing tomato decay observed in this study suggests that it could be a viable alternative for combating pathogen-related decay in tomatoes. This observation aligns with a study reported by [23], who reported that treating various kinds of fruits with chitosan and guava leaf extract significantly increased the shelf life of the fruits. Similarly, our findings are consistent with the report of [24], who highlighted the effectiveness of extracts from medicinal plants like Allium sativum, Azadirachta indica, Mentha arvensis, and Psoralia corlylifolia in preserving fruits from pathogenic and environmental factors.…”
Section: Discussionsupporting
confidence: 93%
“…The effectiveness of neem and moringa aqueous leaf extracts in reducing tomato decay observed in this study suggests that it could be a viable alternative for combating pathogen-related decay in tomatoes. This observation aligns with a study reported by [23], who reported that treating various kinds of fruits with chitosan and guava leaf extract significantly increased the shelf life of the fruits. Similarly, our findings are consistent with the report of [24], who highlighted the effectiveness of extracts from medicinal plants like Allium sativum, Azadirachta indica, Mentha arvensis, and Psoralia corlylifolia in preserving fruits from pathogenic and environmental factors.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to Islam et al . (2021), ascorbic acid was used as a positive control. Ascorbic acid methanolic solution (10 mg mL −1 ) was prepared and serially diluted.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 1 mg mL À1 freeze-dried and spray-dried tea solutions in HPLC-grade water were separately prepared and vortexed. According to Islam et al (2021), with modifications, 0.004% (W/V%) methanolic solution of DPPH (2,2-diphenyl-1-picrylhydrazyl; Sigma-Aldrich) was freshly prepared. After shaking, 1 mL of the DPPH solution was added to 3 mL of the freeze-dried and spray-dried tea aqueous solutions, and the undried tea infusion and the samples were shaken.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
See 1 more Smart Citation